PENERAPAN iLEARNING SURVEY (iSur) DALAM MENINGKATKAN KUALITAS SISTEM INFORMASI SELAMA PROSES PEMBELAJARAN DI PERGURUAN TINGGI RAHARJA - Untung Rahardja; Muhamad Yusup; Ana Nurmaliana (CCIT Journal, 2014)
The accuracy and reliability is the quality of the information. The more accurate and reliable, the more information it’s good quality. Similarly, a survey, the better the survey, the more accurate the information provided. Implementation of student satisfaction measurement to the process of teaching and learning activities on the quality of the implementation of important lectures in order to get feedback on the assessed variables and for future repair. Likewise in Higher Education Prog has undertaken the process of measuring student satisfaction through a distributed questioner finally disemester each class lecture. However, the deployment process questioner is identified there are 7 (seven) problems. However, the problem can be resolved by the 3 (three) ways of solving problems one of which is a system of iLearning Survey (Isur), that is by providing an online survey to students that can be accessed anywhere and anytime. In the implementation shown a prototype of Isur itself. It can be concluded that the contribution Isur system can maximize the decision taken by the Higher Education Prog. By using this Isur system with questions and evaluation forms are submitted and given to the students and the other colleges. To assess the extent to which the campus has grown and how faculty performance in teaching students class, and can be used as a media Isur valid information for an assessment of activities throughout college.